Changes in Word Structure - Usmanova Moxira Kenjaevna (International Journal on Integrated Education, 2021)
The difficulty of phonetic content and morpheme simplification are discussed in this article (expansion of the phonetic structure of the original word). The effect of having multi-syllable phonetic structures was determined as a result of the historical development of the original words, and the structural-semantic, phonetic-derivational development of the words was disclosed.